Financial Performance Mediates the Effect of Sustainability Reporting on Firm Value - Arif, Nariswari Putri; Handayani, Nur (Jurnal Akuntansi Bisnis, 2024)
This study analyzes the effect of economic, environmental, and social aspects of sustainability reporting on firm value, with financial performance as a mediating variable.  A sample of 20 companies from the basic materials and energy sectors listed on the Indonesia Stock Exchange from 2018 to 2022 was analyzed. Multiple linear regression was used to estimate the relationships among the variables, complemented by Sobel tests, to examine the intervening variable's mediating role and address the research gap. The findings reveal that environmental and social aspects positively and significantly impact a firm’s financial performance, unlike the economic aspect. Interestingly, the economic aspect negatively influences firm value, while the environmental aspect demonstrates a significantly positive effect, and the social aspect has no effect. Financial performance has a positive influence on firm value. Furthermore, the study finds that financial performance mediates the relationship between environmental and social aspects of sustainability reporting and firm value, not economic. These results highlight the crucial role of sustainability reporting in enhancing financial performance and ultimately creating long-term value for firms, particularly its environmental and social dimensions. The study emphasizes the need for companies to prioritize these aspects when crafting their sustainability reports to attract investors and achieve sustainable growth.